Folic acid, cobalamin, and biotin concentrations in milk samples of sheep, goats, and cows - Kılıç Altun, S; Durmaz, H; Paksoy, N; Aydemir, ME (Journal of the Hellenic Veterinary Medical Society, 2024)
Milk is an important food obtained from mammals, containing almost all of the nutrients needed for metabolism. The vitamin composition of milk, the first food of mammals, is valuable data for the food industry and public health. This study aimed to determine the levels of folic acid (vitamin B9), cobalamin (vitamin B12), and biotin (vitamin B7) in different milk samples (cow, sheep, goat) using the ELISA method. For this purpose, milk samples from Holstein Cows (n:50), Awassi Sheep (n:50), and Kilis Goats (n:50) available for retail in the Şanlıurfa province of Turkey were collected and analyzed. In this study, the average folic acid content of sheep, goat, and cow milk was found to be 3.45 µg/100 mL, 7.23 µg/100 ml, and 6.64 µg/100 mL, respectively. The average cobalamin content of sheep, goat, and cow milk was 0.70 µg/100 ml, 7.43 µg/100 ml, and 0.58 µg/100 mL, respectively, while the average biotin content of sheep, goat, and cow milk was 2.21 µg/100 mL, 2.21 µg/100 mL, and 2.09 µg/100 mL, respectively. It was noted that the average biotin levels in sheep, goat, and cow milk did not differ significantly. However, significant differences were observed in the quantities of folic acid and cobalamin (P<0.05). Different levels of folic acid were found in milk samples from these three species. Cobalamin levels in goat milk samples were significantly higher, while biotin levels were similar in each milk sample of the species. This study underscores the importance of understanding and considering the diverse vitamin compositions of milk from different mammalian species to ensure comprehensive nutritional intake.